2005
DOI: 10.1097/01.rli.0000166940.72971.4a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Elastography of the Breast

Abstract: A good separation exists between benign and malignant lesions in elasticity, corresponding with specific signal intensity and morphologic data. Further clinical studies with a larger number of patients are needed for extended validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…In a similar study involving 15 healthy volunteers, 15 patients with malignant tumors, and 5 patients with benign lesions, malignant lesions were found to be significantly stiffer than benign lesions, normal breast parenchyma, and adipose tissue (119). Early work looking at the correlation between MRE and CE-MRI in a study involving 20 patients showed good distinction between benign and malignant lesion stiffness which agreed with the morphologic and dynamic data (120). A more recent study involving 68 patients with 39 malignant lesions and 29 benign lesions, and using a more sophisticated elastographic inversion algorithm, reported that while CE-MRI alone had a sensitivity of nearly 100%, but a specificity of 40% and an AUC of 0.88, the elastography results alone provided an AUC of about 0.91, and the combination of CE-MRI and MRE resulted in an AUC of around 0.96 (28).…”
Section: Breast Mresupporting
confidence: 57%
“…In a similar study involving 15 healthy volunteers, 15 patients with malignant tumors, and 5 patients with benign lesions, malignant lesions were found to be significantly stiffer than benign lesions, normal breast parenchyma, and adipose tissue (119). Early work looking at the correlation between MRE and CE-MRI in a study involving 20 patients showed good distinction between benign and malignant lesion stiffness which agreed with the morphologic and dynamic data (120). A more recent study involving 68 patients with 39 malignant lesions and 29 benign lesions, and using a more sophisticated elastographic inversion algorithm, reported that while CE-MRI alone had a sensitivity of nearly 100%, but a specificity of 40% and an AUC of 0.88, the elastography results alone provided an AUC of about 0.91, and the combination of CE-MRI and MRE resulted in an AUC of around 0.96 (28).…”
Section: Breast Mresupporting
confidence: 57%
“…Figure 6 demonstrates that the conventional approach to image reconstruction (NP) employed in breast elastography (Van Houten et al , 2003; Xydeas et al , 2005; Oberai et al , 2009) is not viable in vascular applications—which implies that the ill-posed nature of the inverse elasticity problem is a bigger issue in vascular elastography, perhaps because the incompressibility of soft tissues presents additional problems. More specifically, in vascular elastography the displacement is determined almost entirely by incompressibility and the displacement of the inner vessel wall, and is nearly independent of other mechanical parameters; this lack of sensitivity makes the inverse problem more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The large attenuation effects in MRE can have a significant impact in some areas ([1]), and visualizing viscosity information has been tried for MRE ([21], [24], [25]). Fig.…”
Section: Discussionmentioning
confidence: 99%